ANALISIS PERBEDAAN PENDAPATAN PETANI BINAAN PENYULUH PETANI LAPANGAN (PPL) DENGAN PETANI NON BINAAN PENYULUH PETANI LAPANGAN (PPL) DI KABUPATEN MMIKA (STUDI KASUS DI KAMPUNG WONOSARI JAYA) - Vivilian Bahir; Stepanus Sandy (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2017)
The purposes of this research are (1) to know the significant difference between trained and non trained farmer in Mimika regency. (2) to know the factors that influence the income difference between trained and non trained farmer in Mimika regency.The analysis instruments used to measure the income difference of trained and non trained farmer in Mimika regency are median test.The result of analysis showed that there was a significant difference between the trained and non trained farmer.